(untitled) (Quinto Sol, 2026)
This article aims to explore the analytical potential of migration letters, both as sources and as objects of study in themselves. To this end, four possible ways of analyzing epistolary corpuses are presented: a) the letter as a source, b) the letter as a record of language in use, c) the letter as discourse, and d) the letter as a product. To illustrate these analytical possibilities, a corpus of letters written by European migrants to their relatives and friends during the early years of their lives in Argentina, between the 1850s and 1870s, is examined. It is expected that the proposed guidelines will be applicable to epistles produced in different social, cultural, and historical contexts.